2021
DOI: 10.51847/80jyiklt8c
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Adrenal Estrogen Receptors (ERs) In Pregnant Rabbits Treated with Organic Extract of Bunium incrassatum

Abstract: This research deals with the organic extracts impact of Bunium incrassatum on the immune expression of estrogen receptors that is the assessment of the effect of organic extracts from the seeds of Bunium incrassatum (Apiaceae) on the immune labelling of estrogen receptors in the adrenal gland of pregnant rabbits from the local population (Oryctolagus cuniculus).The work was carried out on pregnant rabbits during the last third of gestation (from day 17 to day 27 of gestation). The animals were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Follicles are well adhered to enclosing an active colloid. An experiment made by Bentayeb et al 25 on the effect of B. incrassatum on the immunological expression of estrogen receptors in the adrenal gland suggested that the organic extract, and its composition, mainly β-Sitosterol and β-caryophyllene, had a modulating activity of estrogen receptor. They had a role in preventing and treating breast cancer and the prevention of osteoporosis.…”
Section: Histological Studymentioning
confidence: 99%
“…Follicles are well adhered to enclosing an active colloid. An experiment made by Bentayeb et al 25 on the effect of B. incrassatum on the immunological expression of estrogen receptors in the adrenal gland suggested that the organic extract, and its composition, mainly β-Sitosterol and β-caryophyllene, had a modulating activity of estrogen receptor. They had a role in preventing and treating breast cancer and the prevention of osteoporosis.…”
Section: Histological Studymentioning
confidence: 99%